ҚАРАҚАЛПАҚ НАҚЫЛ-МАҚАЛЛАРЫНДА УАҚЫТ ҲӘМ КЕҢИСЛИК МӘСЕЛЕЛЕРИ - Зинатдинова, Г.И. (SCIENCE and SOCIETY, 2022)
The article deals with the problem of chronotope (time and space) in the Karakalpak folk proverbs. In organizing this problem, attention is focused on such factors as ethnic point of view, worldview, attitude to nature.
Keywords: chronotope; space and time; lyric chronotope; ethnic point of view; worldview and chronotope